Pancasila Dalam Perspektif Hukum Islam - Lalu Yoga Vandita (TAFAQQUH, 2023)
Pancasila is considered to be something sacred and every citizen must memorize and obey the contents of Pancasila. However, the majority of Indonesian citizens only consider Pancasila as the basis of the state or ideology without paying attention to its meaning and benefits in life. Without people realizing that the values contained in Pancasila are very useful and useful. Indirectly, the values contained in Pancasila are also is a reflection that the founding fathers of Indonesia, the majority of whom were Muslims, really understood the diversity that existed in Indonesia and incorporated the universal principles of Islamic teachings into the Pancasila principles as a middle way solution (wasathan). For this reason, it is very appropriate to say that Pancasila is very Islamic, because it is in line with practice. To obtain relevant results, researchers used qualitative research in the form of a literature study. This category of Islamic research can be included in the normative-empirical type of Islamic legal research. The data sources used include several scientific literature in the form of journals, books, theses or dissertations which examine Islamic law in Indonesia in the context of the Pancasila state.